2010
DOI: 10.1097/brs.0b013e3181d830de
|View full text |Cite
|
Sign up to set email alerts
|

Surgeon Perceptions and Reported Complications in Spine Surgery

Abstract: We define a complication as an unintended and undesirable diagnostic or therapeutic event that may impact the patient's care. Complications should be recorded and analyzed relative to disease severity, patient comorbidities, and ultimately their effect on patient outcomes. Further work needs to be done to develop a complication risk impact index that has the ability to help us assess and communicate the interaction of patient comorbidities and complication severity on patient centered outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
52
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(57 citation statements)
references
References 32 publications
4
52
0
1
Order By: Relevance
“…20 A comprehensive, ideal system for complication analysis would include this graduated complication severity score in addition to a patient-specific comorbidity profile. 7 Ultimately, this approach would allow patient comorbidities and procedural complexity to be integrated for the purpose of the development of a procedure-specific, risk-adjusted predictive model for complications in spinal surgery. 7,17 In the analysis of a large retrospective database, Wang, et al 23 reviewed the Nationwide Inpatient Sample database and reported rates of complications after fusions from 9.02% to 10.5%, compared with an overall prevalence of 3.93% in nonfusion cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…20 A comprehensive, ideal system for complication analysis would include this graduated complication severity score in addition to a patient-specific comorbidity profile. 7 Ultimately, this approach would allow patient comorbidities and procedural complexity to be integrated for the purpose of the development of a procedure-specific, risk-adjusted predictive model for complications in spinal surgery. 7,17 In the analysis of a large retrospective database, Wang, et al 23 reviewed the Nationwide Inpatient Sample database and reported rates of complications after fusions from 9.02% to 10.5%, compared with an overall prevalence of 3.93% in nonfusion cases.…”
Section: Discussionmentioning
confidence: 99%
“…7 Ultimately, this approach would allow patient comorbidities and procedural complexity to be integrated for the purpose of the development of a procedure-specific, risk-adjusted predictive model for complications in spinal surgery. 7,17 In the analysis of a large retrospective database, Wang, et al 23 reviewed the Nationwide Inpatient Sample database and reported rates of complications after fusions from 9.02% to 10.5%, compared with an overall prevalence of 3.93% in nonfusion cases. Additionally, Deyo et al 8 reviewed a Medicare database and determined a complication rate 1.9 times greater in fusion-treated patients than in those who had undergone decompression alone and, more recently, 9 noted an 2.95-fold increase in life-threatening complications after complex fusions compared with decompression alone.…”
Section: Discussionmentioning
confidence: 99%
“…Although surgeons understand the importance of adverse events, tracking and reporting are weaknesses in the clinical and research environment [2,25,43]. A major contributor to these weaknesses lies in the lack of standardized definitions of adverse events [22,34], with variations of the same adverse events identified across studies [4,5,9,22,34]. In response to this deficiency, standardized definitions of adverse events have been proposed [16,17], with the Clavien-Dindo classification being commonly used and reported [7,10].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, a consensus group of surgeons from AOSpine North America has recently met and published on a series of consensus-based systematic reviews on the topic of complications and complications avoidance in spine surgery. 4 The main message, which should always be remembered in surgical practice, is that spine surgery is still an imperfect art. Thus, there is an ongoing need for reanalysis and critical appraisal in order for continued improvement in the growing field of spine surgery.…”
mentioning
confidence: 99%